39 Family presence during resuscitation – a protocol of a cochrane systematic review. (26th April 2019) - Rubin, MA; Herling, SF; Klausen, TW; Jabre, P; Møller, AM
Abstract : Background: Family presence during resuscitation (FPDR) is a growing praxis despite most evidence is of low quality. 1 The aim of this review is to investigate if FPDR might decrease PTSD-related symptoms including signs of depression/anxiety. We also want to explore the effect on medical care and patient survival. Method: We will include randomized controlled trials (RCTs) and perform a meta-analysis after assessment of heterogeneity, if appropriate. For dichotomous outcomes Mantel Haenszel test will be used, for continuous outcomes inverse variance and for rare events, Peto's odds ratio. The quality of evidence will be assessed using the GRADE-method. Results: Preliminary search results identified 564 articles for screening leading to four RCTs. This leads to a sample size of 1388. A cluster-RCT of 570 relatives showed positive effects of FPDR on relatives' psychological outcomes during pre-hospital CPR and no effects on patient mortality or personnel distress. 2 The largest RCT with a sample size of 705 investigated FPDR of paediatric patients, but had a high risk of bias. 3 Conclusion: We hypothesize that there is a lack of high quality research regarding FPDR, but that the evidence indicate an association with overall positive results on relatives' psychological outcomes and that it doesn't affect the healthcare professionals, morbidity, or mortality of the patients negatively. References: Oczkowski SJ, Mazzetti I, Cupido C, Fox-Robichaud AE. The offering of family presence during resuscitation: a systematic review and meta-analysis. Journal of intensive care 2015;3:41. Jabre P, Belpomme V, Azoulay E, Jacob L, Bertrand L, Lapostolle F, et al. Family presence during cardiopulmonary resuscitation. The New England journal of medicine 2013;368(11):1008–18. Dudley NC, Hansen KW, Furnival RA, Donaldson AE, Van Wagenen KL, Scaife ER. The effect of family presence on the efficiency of pediatric trauma resuscitations. Annals of emergency medicine 2009;53(6):777–84.e3. Conflict of interest: P. Jabre is the first author of an included primary study (which she has conducted) in the Cochrane Review (2). She will not extract data from her own study. Instead, M.A. Rubin and A.M. Møller will extract these data, and check the interpretation against the study report and any available study registration details or protocol. Funding: None.